2005
DOI: 10.1002/marc.200500617
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube‐Adsorbed Electrospun Nanofibrous Membranes of Nylon 6

Abstract: Summary: A simple and mass‐producible method was developed to densely assemble multiwalled carbon nanotubes (MWNTs) onto electrospun nylon 6 nanofibrous membranes. The process consists of dispersing the acid‐treated MWNTs in surfactant solutions or organic solvents, and dipping the nanofibrous membranes in the resulting dispersion for only 60 seconds, followed by the extraction of the surfactants in pure water and drying. The conductivity of the MWNT‐adsorbed nanofibrous membranes ranges from 2.2 × 10−2 to 1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 39 publications
0
72
0
Order By: Relevance
“…In order to disperse them in aqueous media, the SDS surfactants were used, which results a homogenous black ink like solutions after sonication. 12 It was observed that the color of the non-woven membranes changes from white to grey due to the presence of MWNTs. The MWNTs were adsorbed not only on the surface of the nanofibers, but also maintained the high porosity of the membranes.…”
Section: Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to disperse them in aqueous media, the SDS surfactants were used, which results a homogenous black ink like solutions after sonication. 12 It was observed that the color of the non-woven membranes changes from white to grey due to the presence of MWNTs. The MWNTs were adsorbed not only on the surface of the nanofibers, but also maintained the high porosity of the membranes.…”
Section: Instrumentationmentioning
confidence: 99%
“…The earlier studies have shown that CNTs have extremely high Young's moduli, similar to that of the in-plane value for graphite (~1 000 GPa). 12 The specific tensile strength of a single layer of a MWNT is 100 times higher than that of steel, and the graphene sheet (in-plane) is stiffer than diamond at low strain. Furthermore, due to their molecular molecular perfection, they are essentially free of defects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figures 1 and 2, the MWCNTs incorporated onto the S-PS/MWCNT microspheres were interconnected, leading to the formation of MWCNTs layers, and the MWCNTs network formed electrical pathways. 25 As mentioned previously, suspension polymerization could control the location of the MWCNTs incorporated into the microsphere because suspension polymerization consists of two phases at the first stage of polymerization and is initiated in the monomer droplet. If the MWCNTs were dispersed in the styrene monomer, the dispersed MWCNTs were well compounded with PS during polymerization, so that they could be located inside the microspheres (I-PS/MWCNT microspheres).…”
Section: Resultsmentioning
confidence: 98%
“…MWNT Oxidation: In order to achieve a strong interaction between the MWNTs and the polyamide fibers, carboxyl groups were grafted on the MWNTs to allow hydrogen bonding, as suggested by Kim et al [24]. The carboxyl groups were created by an acid treatment following our previous work [25].…”
Section: Methodsmentioning
confidence: 99%